Pengaruh Insentif Pajak Di Masa Pandemi Covid-19 Terhadap Kepatuhan Wajib Pajak Di Kabupaten Badung - Merta, I Ketut; Usadha, I Dewa Nyoman (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2023)
This research takes the object of the Badung Regency Revenue Agency with the variables Tax incentives and taxpayer compliance, the aim is to determine the effect of giving tax incentives during the Covid-19 pandemic on taxpayer compliance in Badung Regency. Qualitative research methodology with a questionnaire, population and sample of 100 respondents. Hypothesis: There is a level of influence from the variable giving tax incentives caused by the presence of Covid-19 on a taxpayer compliance. The results of the research on the tax incentive variable simultaneously have a